Pemilihan Tempat Kost Menggunakan Metode Multi Attribute Utility Theory Dan Algoritma A* - Yesy Afrillia; Wahyu Fuadi; Ayu Indah Lestari (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
Overseas students usually have difficulty finding boarding houses around Malikussaleh University. To get information on boarding houses, they have to search manually, so the time needed to find a boarding house can be very long. The purpose of this research is to produce a Geographic Information System that can make it easier for students to find information about the location of boarding houses, provide recommendations in selecting boarding houses, and find the shortest distance for each boarding house to campus. By using the MAUT method combined with an algorithm A* can provide recommendations in selecting boarding houses and provide the shortest distance from the location of each boarding house to the Campus. The results of this study resulted in recommendations for boarding houses based on the results of ranking using the MAUT method. The boarding houses with the top three rankings are 4G Boarding House, Ceiza Boarding House, and Hj Boarding House. Madriah. With distance of 0.75 km, 2.01 km and 1.38 km. With an algorithmA* to find the closest route it can be concluded that the MAUT method and algorithm A* is a combination that can be used in evaluating boarding houses and solutions in searching for the shortest distance.